Learn AWS serverless computing : a beginner's guide to using AWS Lambda, Amazon API Gateway, and services from Amazon Web Services /: a beginner's guide to using AWS Lambda, Amazon API Gateway, and services from Amazon Web Services. (2019) - Patterson, Scott
No abstract available